Comparative Analysis of French and Uzbek Fairy Tales (on the example of the Fairy Tales "Three Brothers Are Heroes" and "The Cat in Boots")" - Rustamova Feruzabonu (Indonesian Journal of Innovation Studies, 2022)
Folklore, especially fairy tales, which is distinguished by its weight in fiction, plays an important role in the proper upbringing of children. The main role of fairy tales in the way of life is to prepare the ground for the young generation to become harmoniously developed people. The article compares the similarities between the Uzbek and French folk tales "Three Brothers" and Charles Perrault's "The Cat in the Etiquette". There were many similarities in the tales created by different cultures, different religions, based on evidence.